1984
DOI: 10.1002/jpln.19841470108
|View full text |Cite
|
Sign up to set email alerts
|

Wirkungen organischer Substanzen auf Boden‐ und Düngerphosphat. Teil 2: Einfluß verschiedener organischer Stoffe auf die Mobilität von Dünger‐P

Abstract: In Modellversuchen wurde die Wirkung langjähriger organischer Düngung sowie von Rottestroh, Maiswurzeln und Gülle als Bebrütungszusatz auf die Diffusion von 32P aus zugesetztem (NH4)2H32PO4 in einem „Bodenblock”︁ bzw. die Fixierungsrate des Düngerphosphates im Boden untersucht. 1. Im „Bodenblockversuch”︁ verbesserte eine Vorbebrütung (7 Tage) mit Gülle (5% Tr. S. zugesetzt zu einer P‐armen Ackerbraunerde) die P‐Diffusion gegenüber dem Kontrollzusatz einer äquivalenten anorganischen P‐Menge. Eine Vorbebrütung m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Treatments where cattle slurry was added together with selenate were found to increase the Se concentration in grain at the higher pH level in both peat and loam. In other studies, it was found that manure reduced the soil retention of phosphate, which is like selenite adsorbed to sesquioxides by ligand exchange (Amberger and Amann 1984;Mnkeni and MacKenzie 1985;Øgaard 1996). This reduction in phosphate retention was explained by the content of lowmolecular-weight organic acids in the manure, and the ability of those acids to occupy binding sites for P in soil (Lopez-Hernandez et al 1979;Amann and Amberger 1988;Gerke 1992).…”
Section: Effect Of Manure On Soil Se Adsorptionmentioning
confidence: 93%
See 1 more Smart Citation
“…Treatments where cattle slurry was added together with selenate were found to increase the Se concentration in grain at the higher pH level in both peat and loam. In other studies, it was found that manure reduced the soil retention of phosphate, which is like selenite adsorbed to sesquioxides by ligand exchange (Amberger and Amann 1984;Mnkeni and MacKenzie 1985;Øgaard 1996). This reduction in phosphate retention was explained by the content of lowmolecular-weight organic acids in the manure, and the ability of those acids to occupy binding sites for P in soil (Lopez-Hernandez et al 1979;Amann and Amberger 1988;Gerke 1992).…”
Section: Effect Of Manure On Soil Se Adsorptionmentioning
confidence: 93%
“…Earlier it was shown that manure application reduced the retention of phosphate (Amberger and Amann 1984;Mnkeni and MacKenzie 1985;Øgaard 1996). This was explained by the content of low-molecular-weight organic acids in the manure which competed with phosphate for the binding sites.…”
Section: Introductionmentioning
confidence: 96%